REVIEW OF THE LITERATURE WITHIN THE FRAMEWORK OF THE DEVELOPMENT OF THE EFFECTIVENESS OF THE WINTER WHEAT IRRIGATION PROCEDURE - Yusupov Hamid; Oripov Imomnazar O’ktamovich; Oripov Imomnazar O’ktamovich (Scholar Express Journals, 2023)
As it is known, in the current era, when climate change has become a global problem due to anthropogenic factors, the period of efficient use of water resources is especially required. The reason is that in recent years, there have been frequent water shortages in the countries of Central Asia, especially in Uzbekistan. For example, until the 2000s, there was a water shortage every 6-8 years, but recently, this situation has been observed every 3-4 years. As a result of this, in 2018, the total water shortage in Uzbekistan will be 3 billion. was m3 . By 2030, this indicator will be 7 billion. m3 , and 13- 15 billion by 2050. It is possible to reach m3. In addition, as a result of the increase in air temperature, it is estimated that the irrigation standards for agricultural crops will increase by 5 percent by 2030, and by 7-10 percent in 2050.
Keywords: soil; water; wheat; Krupinka